Co-creation of Research and Design During a Coding Club With Autistic Students Using Multimodal Participatory Methods and Analysis - Ward, Verity; Parsons, Sarah; Kovshoff, Hanna; Crump, Ben (Frontiers in Education, 2022)
Participatory design aims to work with those who are often excluded from design processes so that their interests are better represented in design solutions. Autistic children are often marginalised and excluded from design processes due to concerns about how their social and communication differences may act as barriers to participation, leading to calls for design processes to be more inclusive and examined more closely to understand the value of participation for (autistic) children and young people. This research describes a participatory design project to develop a computer game during a weekly coding club at a special school. Fourteen autistic (neurodivergent) young people, eight staff members, four technology industry representatives and a Doctoral researcher worked together to design, develop, test and evaluate the game. This paper focuses specifically on the views and experiences of two of the students, which are captured primarily through a Digital Story. Digital Stories are short student-centred videos which show educational experiences. We use a social semiotic multimodal approach to analysis which does not prioritise linguistically encoded meaning, instead recognising the importance and validity of the many and varied ways in which students contributed to the project. The findings highlight the valuable opportunities that participatory design processes can provide for students as both learners and as expert knowers. It emphasises the need to allow room for students’ agency in the design process, so that they really can have a say in the outcomes of design and feel ownership over the process and outcomes of their research participation.